Low Molecular Weight Heparin in Portal Vein Thrombosis of Cirrhotic Patients: Only Therapeutic Purposes?. (29th December 2014) - Licinio, Raffaele; Principi, Mariabeatrice; Losurdo, Giuseppe; Castellaneta, Nicola Maurizio; Ierardi, Enzo; Di Leo, Alfredo
Abstract : Cirrhosis has always been regarded as hemorrhagic coagulopathy caused by the reduction in the hepatic synthesis of procoagulant proteins. However, with the progression of liver disease, the cirrhotic patient undergoes a high rate of thrombotic phenomena in the portal venous system. Although the progression of liver failure produces a reduction in the synthesis of anticoagulant molecules, a test able to detect the patients with hemostatic balance shifting towards hypercoagulability has not yet been elaborated. The need of treatment and/or prophylaxis of cirrhotic patients is demonstrated by the increased mortality, the risk of bleeding from esophageal varices, and the mortality of liver transplantation, when portal vein thrombosis (PVT) occurs even if current guidelines do not give indications about PVT treatment in cirrhosis. In view of the general feeling that the majority of cirrhotic patients at an advanced stage may be in a procoagulant condition (suggested by the sharp increase in the prevalence of PVT), it is presumable that a prophylaxis of this population could be of benefit. The safety and the efficacy of prophylaxis and treatment with enoxaparin in patients with cirrhosis demonstrated by a single paper suggest this option only in controlled trials and, currently, there are no sufficient evidences for a recommendation in the clinical practice.